A Boy with Nephrotic Syndrome and Methemoglobinemia: A Diagnostic Challenge - Sultana, Azmeri; Roy, Ranjit Ranjan; Muinuddin, Golam; Khan, Mohammad Anwar Hossain; Mahmud, Shahabuddin (Journal of Pediatric Nephrology, 2021)
Methemoglobinemia is a rare disease characterized by the elevated levels of methemoglobin in the blood. It may be congenital or acquired. Co-trimoxazole is an antibiotic that belongs to the sulfone group. Sulfone group drugs may produce drug-induced acquired methemoglobinemia. Methemoglobin is an oxidized form of hemoglobin that has an increased affinity to oxygen and a reduced ability to release oxygen to tissues. High levels of methemoglobin inred blood cells cause tissue hypoxia. This disorder may present with several symptoms such as cyanosis, fatigue, dyspnea, and headache. Because it is a rare cause of cyanosis and hypoxemia, the diagnosis of methemoglobinemia is often delayed. We herein discuss a five-year-old boy with steroid-resistant nephrotic syndrome who presented with exertional dyspnea and cyanosis and was later diagnosed as a case of co-trimoxazole-induced methemoglobinemia.